2002
DOI: 10.1051/rnd:2002041
|View full text |Cite
|
Sign up to set email alerts
|

Protein degradation in the rumen of red clover forage at various stages of growth and conserved as silage or wrapped big bales

Abstract: -In order to study the extent to which rumen soluble nitrogen can contribute to the intestinal flow, a study was carried out to simultaneously assess the dynamics of protein disappearance from dacron bags placed in the rumen and the amount of various N products in the rumen fluid (total nitrogen (tN), ammonia nitrogen (NH3-N), non-ammonia nitrogen (NAN)). The measurements were carried out on 4 sheep fed successively various red clover forages. These forages included the initial growth of fresh red clover (50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…Broderick and Albrecht (1997) demonstrated a lower rumen degradation rate of protein in red clover than in white clover, but in our study the fractional rate of protein degradation was similar for white clover and red clover, which was substantially higher than for the grass species. However, the ruminal protein degradation rate in red clover can vary from 7.5 to 35.5%/h depending on growth stage and conservation method (Aufrère et al, 2002). The fractional rate of rumen NDF degradation for red clover silage was comparable to values reported by Hoffman et al (1997), similar to the degradation rate of NDF for white clover silage and higher than that of the grass silages.…”
supporting
confidence: 57%
“…Broderick and Albrecht (1997) demonstrated a lower rumen degradation rate of protein in red clover than in white clover, but in our study the fractional rate of protein degradation was similar for white clover and red clover, which was substantially higher than for the grass species. However, the ruminal protein degradation rate in red clover can vary from 7.5 to 35.5%/h depending on growth stage and conservation method (Aufrère et al, 2002). The fractional rate of rumen NDF degradation for red clover silage was comparable to values reported by Hoffman et al (1997), similar to the degradation rate of NDF for white clover silage and higher than that of the grass silages.…”
supporting
confidence: 57%
“…Significant differences in both asymptote and rate of degradation were found among substrates incubated, which demonstrate that the technique is sensitive to forages having different chemical composition and nutritive value. The estimated values of the parameters of the curve were comparable to those obtained using the conventional in situ degradability technique as reported by Huntington and Givens (1995) for grass hay, Ørskov et al (1988) for barley straw, Aufrère et al (2003) for perennial ryegrass and Aufrère et al (2002) for red clover.…”
Section: Degradation Of Substrates Within Nylon Bagssupporting
confidence: 85%
“…The soluble protein fraction (a) is comprised of fine particles, intact protein, and non-protein N -NPN, which contains peptides, and it is not completely degraded in the rumen (Gierus et al, 2005) and between 7 and 13% of the non-ammonia N (NAN) escapes the rumen (Aufrère et al, 2002), suggesting a possible overprediction of RDP. Interestingly, Broderick et al (2010) meta-analyzed data of 32 studies and reported that the NRC (2001) underpredicted RDP (i.e., overpredicted RUP) by 22% than observed omasal values.…”
Section: Description Of Major Feeding Systemsmentioning
confidence: 99%